ANALISIS STUDI KELAYAKAN PERENCANAAN PEMBANGKIT LISTRIK TENAGA SURYA (PLTS) DENGAN SISTEM ON GRID DI GEDUNG KAMPUS UTAMA SEKOLAH TINGGI TEKNOLOGI (STITEK) BONTANG - Tamara Gresiela Panduwaal; Turahyo; Arfittariah (Sekolah Tinggi Teknologi Bontang, 2025)
The increasing demand for electricity in Indonesia calls for the utilization of renewable energy. One of the solutions is the On-Grid Solar Power Plant (PLTS). An On-Grid PLTS operates by connecting the solar power system directly to the PLN electricity grid without the use of batteries, allowing the generated energy to be used immediately while any surplus can be exported to the grid. The designed PLTS uses monocrystalline solar modules with a capacity of 555 Wp and a 25 kWp inverter. The planning of this On-Grid PLTS system at the Main Campus Building of STITEK Bontang includes an investment feasibility analysis using the Net Present Value (NPV), Discounted Payback Period (DPP), and Internal Rate of Return (IRR) methods. The analysis results show an NPV of IDR 3,213,800,156, proving that this investment is profitable. Additionally, a DPP of 10 years and 4 months indicates a relatively quick return on investment, while an IRR of 11.5%, higher than the discount rate, confirms the project's financial feasibility. The On-Grid PLTS contributes to energy savings of up to 28%, reduces dependence on fossil fuels, and supports the Green Campus concept. By harnessing the abundant solar energy, this system becomes an ideal solution for educational institutions transitioning towards sustainable energy